Recent Advances in Research of Plant Virus Movement Mediated by Triple Gene Block - Solovyev, Andrey; Kalinina, Natalia; Morozov, Sergey (Frontiers in Plant Science, 2012)
The aim of this short review was to summarize recent advances in the field of viral cell-to-cell movement mediated by the triple gene block (TGB). The growing body of new research has uncovered links between virus cell-to-cell trafficking and replication, silencing suppression, virus spread over the plant, as well as suggested the roles of nucleus/nucleolus in plant virus transport and revealed protein-membrane associations occurring during subcellular targeting and cell-to-cell movement. In this context, our review briefly summarized current views on several potentially important functions of TGB proteins and on the development of new experimental systems that improved understanding of the molecular events during TGB-mediated virus movement.